The relationship between an online mindfulness intervention and academic achievement, attendance, behavior, and social-emotional growth in 9th grade students - Biery, Jana Lauren (Kansas State University, 2022)
The challenges facing adolescents today are greater than ever. It is imperative that students have the social and emotional skills to help them succeed. Mindfulness helps support social, emotional, and academic learning as it assists children in becoming more self-aware and builds self-regulation. Mindfulness is about being present within yourself as well as within your environment. A review of the literature provided evidence supporting the feasibility and effectiveness of mindfulness-based interventions for adolescents. Fully present teachers and students can experience strong emotion management and stress reduction, which in turn can lead to improved attention, positive academic outcomes, reduced behavior problems, and an increased enthusiasm for learning. This quasi-experimental study examined the relationship between a whole school online mindfulness intervention and student academic performance, attendance, behavior and social emotional growth at one midwestern high school. The researcher collected student aReading and aMath test scores, attendance percentages, number of discipline referrals, and mySAEBRS scores from a fall semester during which an online mindfulness intervention was being utilized from the following fall semester. Using one-way ANOVAs and two proportion z tests, the findings revealed statistically significant differences for behavior referrals and social-emotional growth between the years with and without the online mindfulness intervention.
Keywords: Mindfulness; Online-mindfulness intervention; Mental health; Social-emotional growth; Academic achievement; Behavior; Attendance; High school